Presença das Tecnologias da Informação e Comunicação nas pesquisas em Educação Ambiental: uma análise de periódicos da área - Oliveira, Alexander (Universidade Federal de São Carlos, 2025)
Environmental education, despite already being present in students' initial formation on within schools, has not demonstrated the necessary efficiency to raise student awareness regarding the environmental problems we currently face. Therefore, this study aims to investigate the use of Information and Communication Technologies (ICTs) in Environmental Education (EE) research by analyzing the strategies, challenges, and benefits of these technologies within the field through specialized journals. This work integrates the study of 12 articles, selected from the four main electronic scientific journals focused on environmental education, which address the use of ICTs in EE. The articles collected for this bibliographic research were published between 2015 and 2025. The analysis highlights the great potential of new technologies to raise awareness in a playful, dynamic, and more efficient manner, promoting student agency and interdisciplinarity. However, the study also warns of crucial challenges, such as the digital divide and the need for teacher training to ensure the full integration of these tools.
Presence of Information and Communication Technologies in Environmental Education Research: an Analysis of Journals in the Field
Keywords: TICs; Tecnologias da Informação e Comunicação; Educomunicação; Educação Ambiental; Information and Communication Technologies; Educommunication; Environmental Education; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade